Lactose tolerance test as an alternative to hydrogen breath test in the study of lactose malabsorption - Sendino Teresa (De Gruyter, 2020)
Lactose malabsorption is generally assessed by hydrogen breath testing (HBT). However, this test is not recommended in patients with high baseline hydrogen concentrations (H2B). In addition, breath testing is not recommended in the current situation created by the COVID-19 pandemic, due to the potential infectiveness of the samples. The objective is to assess concordance between HBT and lactose tolerance test (LTT) depending on H2B concentrations.